2019
DOI: 10.2139/ssrn.3441914
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-Driven Gene Expression (EDGE) Enables the Generation of Viral Vectors Specific to Neuronal Subtypes

Abstract: Although a variety of remarkable molecular tools for studying neural circuits have recently been developed, the ability to deploy them in particular neuronal subtypes is limited by the fact that native promoters are almost never specific enough. We recently showed that one can generate transgenic mice with anatomical specificity surpassing that of native promoters by combining enhancers uniquely active in particular brain regions with a heterologous minimal promoter, an approach we call EDGE (Enhancer-Driven G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The construction of these virus, AAV-TRE-tight-GFP and AAV-TRE-tight-oChIEF-Citrine respectively, has been described in Nilssen et al (2018) Subsequently, the mCherry sequence was synthesized and cloned in an inverted orientation into EcoR1 and BamH1 sites in pAAV-CMV-FLEX-MCS-WPRE to make pAAV CMV-FLEX-mCherry-WPRE. AAV-CMV-FLEX-mCherry was recovered from pAAV CMV-FLEX-mCherry-WPRE as described elsewhere (Nair et al, 2020;Nilssen et al, 2018).…”
Section: Surgical Procedures and Virus/tracer Injectionsmentioning
confidence: 99%
“…The construction of these virus, AAV-TRE-tight-GFP and AAV-TRE-tight-oChIEF-Citrine respectively, has been described in Nilssen et al (2018) Subsequently, the mCherry sequence was synthesized and cloned in an inverted orientation into EcoR1 and BamH1 sites in pAAV-CMV-FLEX-MCS-WPRE to make pAAV CMV-FLEX-mCherry-WPRE. AAV-CMV-FLEX-mCherry was recovered from pAAV CMV-FLEX-mCherry-WPRE as described elsewhere (Nair et al, 2020;Nilssen et al, 2018).…”
Section: Surgical Procedures and Virus/tracer Injectionsmentioning
confidence: 99%
“…However, we postulated that by integrating multiple sources of data we could increase our confidence in the candidate pREs. Thus, we combined our H3K27Ac screen with previously published DLX2, LHX6 and NKX2-1 TF ChIP-seq (Lindtner et al, 2019;Sandberg et al, 2016) found that only half of the tested AAVs targeted cells in a similar pattern to the corresponding transgenic line (Nair et al, 2020). Despite improvements in computational RE prediction methods, this is likely to mean that individual candidates will continue to need empirical testing.…”
Section: Epigenetic Screen For Candidate Cin Enhancersmentioning
confidence: 99%
“…Identifying functional enhancers using AAV reporter vectors. To determine whether ATAC-seq peaks might provide useful enhancers for developing novel genetic tools as had been previously shown (Dimidschstein et al, 2016;Nair et al, 2020) we cloned several peaks into a reporter AAV vector backbone and packaged viral particles with the mouse blood-brain barrierpenetrant capsid PHP.eB (Fig. 3A, Chan et al, 2017).…”
Section: Concordance Of Epigenetic Marks In Human Neurons From Distinmentioning
confidence: 99%
“…AAV capsids have been identified that possess unique tropisms like retrograde transport (Tervo et al, 2016), and blood brain barrier penetrance (Deverman et al, 2016;Chan et al, 2017), and can be exploited to deliver specific transgenes in many tissues (Deverman et al, 2016;Greig et al, 2018;Song et al, 2019). Specific promoters and enhancers can be used to further control transgene expression (Nord et al, 2013;Visel et al, 2013;Silberberg et al, 2016;Dimidschstein et al, 2016;Xiong et al, 2019;Jüttner et al, 2019;Nair et al, 2020). The genome capacity of AAV is ~4.7kb, so only small gene regulatory elements (i.e.…”
Section: Introductionmentioning
confidence: 99%